THE NIGERIA STATE AND PEASANTS: ANTIMONIES OF MARGINALISED SOCIAL CATEGORY - NWOYE, Kenneth Ogechukwu (Social Science Research, 2021)
This paper explores the way and manner the Nigerian state responds to changing demands of peasants and how successive policies and programmes tend to undermine, marginalize and destroy the peasants’ way of life. Despite enormous state pressure and control, the peasantry has continued to resist change and adaption not necessarily because of their strength as a group but largely due to failure of state policies and programmes to integrate and subdue them. Using the class theory, the study explores the conflicting and often contradictory relationship between the state and peasant in Nigeria. It concludes that the peasantry, despite years of repressive state policies, remains a strong potent social force and that we need more theoretical and methodological search for us to come to terms with complexities of peasant mode of behaviour